2021
DOI: 10.1002/hbm.25618
|View full text |Cite
|
Sign up to set email alerts
|

Shared and distinct brain fMRI response during performance of working memory tasks in adult patients with schizophrenia and major depressive disorder

Abstract: Working memory (WM) impairments are common features of psychiatric disorders. A systematic meta‐analysis was performed to determine common and disorder‐specific brain fMRI response during performance of WM tasks in patients with SZ and patients with MDD relative to healthy controls (HC). Thirty‐four published fMRI studies of WM in patients with SZ and 18 published fMRI studies of WM in patients with MDD, including relevant HC, were included in the meta‐analysis. In both SZ and MDD there was common stronger fMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 166 publications
(199 reference statements)
3
10
0
Order By: Relevance
“…Additional clusters were located in frontal areas (middle frontal gyrus and inferior frontal gyrus) and may indicate MDD-associated impairments in executive components of WM, such as mental refreshing of recently presented triggers and updating (continuous removal and addition of information to WM) ( Nee et al, 2013 ). These findings are in line with previous studies ( Garrett et al, 2011 , Meusel et al, 2013 , Vasic et al, 2009 , Wang et al, 2021 , Xia et al, 20192019 , Zhu et al, 2018 ). Divergent from Wang’s et al ( Wang et al, 2015 ) meta-analysis, no frontal hyperactivations were detected in our MDD sample.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Additional clusters were located in frontal areas (middle frontal gyrus and inferior frontal gyrus) and may indicate MDD-associated impairments in executive components of WM, such as mental refreshing of recently presented triggers and updating (continuous removal and addition of information to WM) ( Nee et al, 2013 ). These findings are in line with previous studies ( Garrett et al, 2011 , Meusel et al, 2013 , Vasic et al, 2009 , Wang et al, 2021 , Xia et al, 20192019 , Zhu et al, 2018 ). Divergent from Wang’s et al ( Wang et al, 2015 ) meta-analysis, no frontal hyperactivations were detected in our MDD sample.…”
Section: Discussionsupporting
confidence: 94%
“…N-back performance (defined as hit rate minus false alarm rate) and reaction time during correct responses were used as outcome scores for behavioral analyses. The n-back task has been widely used in MDD to measure working memory processes in fMRI such as updating or manipulation ( Nikolin et al, 2021 , Wang et al, 2021 ). The simplest level (0-back) serves as a baseline since no items need to be updated in working memory and mainly attentional processes are measured ( Harvey et al, 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Meir and colleagues showed that electrical or optogenetic activation of the cholinergic system is able to shift cortical activity to an asynchronous state, which improved sensory responses (141). These effects of NMS could at least partly explain the results of a systematic meta-analysis on working memory tasks in patients with schizophrenia or with major depressive disorder which found common stronger fMRI responses in prefrontal and anterior cingulate cortices, two regions belonging to the DMN (142). In contrast, two independent studies showed that activation of the LC-norepinephrine system increases low-frequency synchronous fMRI connectivity within multiple cortical networks, including the DMN (138,139).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Furthermore, Cao et al (2021) suggested that MDD patients had abnormal connectivity between the right inferior parietal lobule and the right DLPFC. Therefore, overactivity in the PFC of MDD patients occurs in order to compensate for a lack of deactivation in regions of the default mode network (DMN) (Wang et al, 2021). Gärtner et al (2018) demonstrated that MDD patients had higher levels of activity in the left DLPFC and the dACC.…”
Section: Discussionmentioning
confidence: 99%